Animal spirits and credit spreads in a model with a cost channel - Peter Bofinger; Sebastian Debes; Johannes Gareis; Eric Mayer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Shocks in the financial sector caused the great recession of 2008 and pulled down the real economy. To implement financial dynamics in a stylized DSGE-framework we use behavioral elements in expectations to produce waves of bull and bear cycles in the financial intermediation process, that have repercussions on the business cycle dynamics. Our main findings suggest that rapid interest rate reduction and a countercyclical equity regulation in the finance sector can well prevent severe recessions.
Keywords: E32; E52; G21; 330; Animal spirits; bank regulation; financial intermediation; monetary policy